The Principle of Phase Transition Cosmology: The Current Universe Formed by the Evolution of Two-Component Quantum Superfluid - Xiaodong Yang; Yuchen Yang; Zhen Luo; Yuanbo Bi (Reports in Advances of Physical Sciences, 2025)
This paper aims to demonstrate that modern cosmology has overlooked the systematic and holistic aspects of the universe’s evolution. It is based on the notion that the primordial universe comprised a two-component quantum superfluid and a synthesis of contemporary astronomical observations and related theories. This synthesis allows for a renewed understanding of the universe’s systematic evolution, from the general concept of phase transitions and matter condensation to uncovering the physical significance of space and time across the grand epochs of nature. The paper seeks to comprehend, as simply and comprehensively as possible, how the universe functions. It introduces the principle of phase transition cosmology (PTC), grounded in modern cosmology and recent advancements in physical research, elucidating the fundamental implications of PTC. The paper also introduces the concept of cosmological phase transition (CPTR), striving to broaden the application of phase transition principles from condensed matter physics. The paper provides an exhaustive analysis of the corrections that PTC brings to modern cosmology, including the presence of a quantum entanglement epoch in the early universe during its evolution, the assertion that the “Big Bang” was a cosmological phase transition, the nonexistence of cosmic inflation, the formation of early celestial bodies preceding the first batch according to modern cosmology and a slightly older age of the universe than that determined by modern cosmology. The paper further engages in profound discussions on significant issues and proposes observational and experimental verifications in cosmology and physics to substantiate the PTC.